2021
DOI: 10.1007/s12648-020-01995-x
|View full text |Cite
|
Sign up to set email alerts
|

On Einstein equations with cosmological constant in braneworld models

Abstract: In this paper, we investigate the Einstein equations with cosmological constant for Randall-Sundrum (RS) and Dvali-Gabadadze-Porrati (DGP) models to determine the warp functions in the context of warp product spacetimes. In RS model, it is shown that Einstein's equation in the bulk is reduced into the brane as a vacuum equation, having vacuum solution, which is not affected by the cosmological constant in the bulk. In DGP model, it is shown that the Einstein's equation in the bulk is reduced into the brane and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this chapter, we review the action and equations of motion associated with the DGP brane model. In the presence of sources, DGP gravitational action takes the form [9]…”
Section: Action and Equation Of Motionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this chapter, we review the action and equations of motion associated with the DGP brane model. In the presence of sources, DGP gravitational action takes the form [9]…”
Section: Action and Equation Of Motionmentioning
confidence: 99%
“…So far, we have shown that the resulting spacetime metric on the brane is simply a family of RNTNdS type solutions in Einstein-Maxwell theory with the cosmological constant. However, in the corresponding equation of motion (9), there is a second rank tensor , which originates from the projection of the five-dimensional Weyl…”
Section: E µνmentioning
confidence: 99%
See 2 more Smart Citations